John Doe - Moses, Antoinette (Cambridge English readers. Level 1, 1999)
The man they call John Doe lies in a hospital bed. He watches and thinks but says nothing. The doctor wants to know who he is. But John Doe doesn't answer his questions. Then, after John Doe leaves hospital, the doctor finds out more about him than just his real name.